THE INFLUENCE OF WORK-FAMILY CONFLICT ON EMPLOYEE SILENCE AMONG EMPLOYEES OF SECONDARY EDUCATION AL-HIDAYAH MEDAN INDONESIA - Nurul Atikah; Dhian Maulidya; Suchroni Panjaitan; Khairunnisa Khairunnisa (Universitas Islam Sumatera Utara (UISU), 2018)
Employee silence is used by employee in Indonesia as the way to solve the problem. Being silent, the employee tends to withhold the information that might be necessary for the organization. The silent employee affects the work-family conflict. This research is aimed to investigate the influence of work-family conflict on employee silence of SMP Al-Hidayah Medan. Quantitative research methodology (Ary et.all, 2002) is used in conducting and analyzing the data. The data were collected by applying relevant questionnaires. There are 10 respondents in this study, consisting of 5 females (50%) and 5 males (50%). SPSS Statistics software is used in analyzing the data. The finding reveals that Work-family conflict has a significant effect on employee silence. The result also parades that Work-family conflict has contributed 84.5% to employee silence and 15.5% to other factors outside the Work-family conflict described in this study. It indicates that employee silence does not only occur cause of Work-family conflict but also by other factors. It could be the further research about the causes of employee silence.